PENINGKATAN PENGUASAAN KONSEP MAHASISWA CALON GURU PGSD MELALUI PENERAPAN MODEL PEMBELAJARAN INQUIRI LABORATORIUM - Apriyandi Putra, Riki (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This research is aim to know the influence applying model in learning inkuiry laboratory toward concept mastery of students the candidate of teacher elementary school. The subject of this research is the students of program teacher learning of elementary school (PGSD) who take this subject basic concept sains 2 (IPA 2) with the total students that become sample a lot of fourty seven 47 person (in one class), with used purposive sampling. The concept of mastery students is selected by instrument test. The result of this research show that happen significant improvement with the total N-gain is 0,68 (in the middle category). All of the whole students very happy and like in model applying in learning inkuiry laboratory, because they can to help in get knowledge about concepts sains.Key Words: model learning inkuiry laboratory,students concept mastery.